AbdulHamid AbuSulayman's contribution to intellectual and educational reform - Al-Hidabi, Dawood Abdulmalek Yahya (International Institute for Muslim Unity (IIMU), 2024)
This edited book, entitled AbdulHamid AbuSulayman’s Contributions to Intellectual and Educational Reform, brings to light the ideas, thoughts, experiences, and contributions of AbdulHamid AbuSulayman to intellectual and educational reform presented in the scholarly writings and personal narratives of different scholars who contributed to this work. Also, this book is the outcome of a research grant sponsored by the International Institute of Islamic Thought (IIIT) that includes the sponsorship of the international conference on the contributions of AbdulHamid AbuSulayman to intellectual and educational reform. The most important effort made by AbdulHamid in the course of his career was his contribution to establishing and managing institutions and ensuring their continuity, namely: the Association of Muslim Social Scientists in the United States of America, the World Assembly of Muslim Youth, al-Manarat Schools, the World Federation of Islamic Student Organizations, the American Journal of Islamic Social Sciences, the International Institute of Islamic Thought, the Fairfax Institute, the Child Development Foundation, International Islamic University Malaysia with special reference to the Kulliyyah of Islamic Revealed Knowledge and Human Science, which today is named as AbdulHamid AbuSulayman Kulliyyah of Islamic revealed Knowledge and Human Sciences.